The Functional and Neurobiological Properties of Bad Taste - Schier, Lindsey A. (Physiol Rev, 2019)
The gustatory system serves as a critical line of defense against ingesting harmful substances. Technological advances have fostered the characterization of peripheral receptors and have created opportunities for more selective manipulations of the nervous system, yet the neurobiological mechanisms underlying taste-based avoidance and aversion remain poorly understood. One conceptual obstacle stems from a lack of recognition that taste signals subserve several behavioral and physiological functions which likely engage partially segregated neural circuits. Moreover, although the gustatory system evolved to respond expediently to broad classes of biologically relevant chemicals, innate repertoires are often not in register with the actual consequences of a food. The mammalian brain exhibits tremendous flexibility; responses to taste can be modified in a specific manner according to bodily needs and the learned consequences of ingestion. Therefore, experimental strategies that distinguish between the functional properties of various taste-guided behaviors and link them to specific neural circuits need to be applied. Given the close relationship between the gustatory and visceroceptive systems, a full reckoning of the neural architecture of bad taste requires an understanding of how these respective sensory signals are integrated in the brain.